IDENTIFICATION AND ESTIMATION OF THE INFLUENCE OF GENERAL MACROECONOMIC FACTORS ON CHANGES IN COUNTRY’S TAX CULTURE - Maksvytienė, Inga; Šinkūnienė, Kristina (Ekonomika, 2012)
The article presents the concept of tax culture by accentuating the possibilities of tax culture expression. The general factors that influence changes in tax culture are distinguished and defined. The general macroeconomic factors that influence changes in tax culture are presented. Based on the aforementioned factors, changes in the tax culture of Member States and the macroeconomic factors are analyzed in their entirety, and the influence of such factors on the changes of tax culture is calculated and assessed.